Pleaseee help last question
Pleaseee help last question - 1

Answers

Answer 1
Answer:

P(Larger or blue) = 7/10. In a bag we have blue and red marbels, which are large and small as in the table shown in the image, the probability of taking a large or blue marble is 7/10.

The key to solve this problem is find the probability of the union events using the equation P(A∪B) = P(A) + P(B) - P(A∩B).

For this problem we have P(Large or Blue) = P(Large) + P(Blue) - P(Large and Blue). The total of the large ones is 25 and the small ones is 15, meaning that the sum of both is 40. P(large) = 25/40, P(Blue) 20/40, and P(Large and Blue) = 17/40

P(Large or Blue) = 25/40 + 20/40 - 17/40 = 28/40 dividing by 4 both terms of the fraction.

P(large or Blue) = 7/10


Related Questions

A recipe calls for a total of 3 cups flour and sugar. If the recipe calls for a cup of sugar, how much flour is needed?o 3 te cups3 cups4 cups3 cups512 cup313 cups
How many times does 36 go into 180
Can you help me with this?​
13. Mr. Smith teaches history and math classes. He has 25 students in both classes combined. He has 17 students in the math class and 15 students in the history class. Is it possible that 12 stu- dents are enrolled in both his history and his math classes?!
The table shows a relationship between and y-values.which statement describes the pattern created by the values?» Each y value is determined bymultiplying each x value by 3, so thepattern is multiplicative» Each y value is determined by adding4 to each x value, so the pattern isadditive» Each y-value is determined by adding2 to each value, so the pattern isadditive» Each y value is determined bymultiplying each value by 2, so thepattern is multiplicativeDone

66
4
1 5
-8
If A = 7
-4
and B = | 9
-5 -8
find 3A + 9B.

Answers

Answer:

456yup 89i28993728128828282 6r3235

664r5790

BRAINLEST Find the sum of the first 6 terms of the infinite series: 1 - 2 + 4 - 8+...

Answers

Answer:

-21

Step-by-step explanation:

1-2+4-8+16-32

=-21

Answer:

The sum of the first 6 terms of the infinite series will be - 21.

Step-by-step explanation:

In this case, the infinite geometric series 1 - 2 + 4 - 8 + ... is represented by the following summation,

\sum _{{k=0}}^{{n}}(-2)^(k)

Therefore if we continue this pattern, the first 6 terms will be 1 - 2 + 4 - 8 + 16 - 32. Adding these terms,

1 - 2 + 4 - 8 + 16 - 32

= - 1 + 4 - 8 + 16 - 32

= 3 - 8 + 16 - 32 = - 5 + 16 - 32

= 11 - 32 = Solution : - 21

In the past, 21% of all homes with a stay-at-home parent, the father is the stay-at-home parent. An independent research firm has been charged with conducting a sample survey to obtain more current information. (a) What sample size is needed if the research firm's goal is to estimate the current proportion of homes with a stay-at-home parent in which the father is the stay-at-home parent with a margin of error of 0.09? Use a 95% confidence level. (Round your answer up to the nearest whole number.)

Answers

Answer:

A sample size of 79 is needed.

Step-by-step explanation:

In a sample with a number n of people surveyed with a probability of a success of \pi, and a confidence level of 1-\alpha, we have the following confidence interval of proportions.

\pi \pm z\sqrt{(\pi(1-\pi))/(n)}

In which

z is the zscore that has a pvalue of 1 - (\alpha)/(2).

For this problem, we have that:

\pi = 0.21

The margin of error is:

M = z\sqrt{(\pi(1-\pi))/(n)}

95% confidence level

So \alpha = 0.05, z is the value of Z that has a pvalue of 1 - (0.05)/(2) = 0.975, so Z = 1.96.  

What sample size is needed if the research firm's goal is to estimate the current proportion of homes with a stay-at-home parent in which the father is the stay-at-home parent with a margin of error of 0.09?

A sample size of n is needed.

n is found when M = 0.09. So

M = z\sqrt{(\pi(1-\pi))/(n)}

0.09 = 1.96\sqrt{(0.21*0.79)/(n)}

0.09√(n) = 1.96√(0.21*0.79)

√(n) = (1.96√(0.21*0.79))/(0.09)

(√(n))^(2) = ((1.96√(0.21*0.79))/(0.09))^(2)

n = 78.68

Rounding up to the nearest whole number.

A sample size of 79 is needed.

By what factor is z multiplied to get z1?

Answers

Answer:

The correct answer is -2.

Step-by-step explanation:

"z" = 3+2i, which is (3, 2i) on the graph. You must multiply -2 by 3 and 6, which will give you the plot points for z1, (-6, -4i).

A negative number multiplied into a positive number will result in a negative number.

Therefore, -2 is the correct answer.

Answer:

-2

Step-by-step explanation:

just did it

If x = 3 cm and z = 5 cm, what is the length of y?

Answers

Answer:

15cm

Step-by-step explanation:

Solve the equation
- 1
- m - 7 = 5
3

Answers



1/3m-7=5

One solution was found :

m = 36
Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

1/3*m-7-(5)=0

Step by step solution :

Step 1 :

1
Simplify —
3
Equation at the end of step 1 :

1
((— • m) - 7) - 5 = 0
3
Step 2 :

Rewriting the whole as an Equivalent Fraction :

2.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 3 as the denominator :

7 7 • 3
7 = — = —————
1 3
Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

Adding fractions that have a common denominator :

2.2 Adding up the two equivalent fractions
Add the two equivalent fractions which now have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

m - (7 • 3) m - 21
——————————— = ——————
3 3
Equation at the end of step 2 :

(m - 21)
———————— - 5 = 0
3
Step 3 :

Rewriting the whole as an Equivalent Fraction :

3.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 3 as the denominator :

5 5 • 3
5 = — = —————
1 3
Adding fractions that have a common denominator :

3.2 Adding up the two equivalent fractions

(m-21) - (5 • 3) m - 36
———————————————— = ——————
3 3
Equation at the end of step 3 :

m - 36
—————— = 0
3
Step 4 :

When a fraction equals zero :

4.1 When a fraction equals zero ...
Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.

Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.

Here's how:

m-36
———— • 3 = 0 • 3
3
Now, on the left hand side, the 3 cancels out the denominator, while, on the right hand side, zero times anything is still zero.

The equation now takes the shape :
m-36 = 0

Solving a Single Variable Equation :

4.2 Solve : m-36 = 0

Add 36 to both sides of the equation :
m = 36

One solution was found :

m = 36

I happen this help